Undivided Retromandibular Vein Leading to the Absence of External Jugular Vein - Rao, Y. Lakshmisha; Ballal, Vaishnavi; Murlimanju, B. V.; Pai, Mangala M.; Tonse, Mamatha; Krishnamurthy, Ashwin (Journal of Morphological Sciences, 2018)
We report a case of undivided retromandibular vein (RV) that was associated with the absence of external jugular vein (EJV). This variation in the jugular venous system was observed on the right side of the neck of a male cadaver. The posterior auricular vein drained into the RV, which joined the facial vein resulting in a common trunk. This common trunk then drained directly into the internal jugular vein (IJV) thus bypassing the whole venous drainage area of the EJV. It is believed that the knowledge about the venous variations, as in the present case, is enlightening to the clinicians. The preoperative evaluation of the venous system is essential to prevent complications like catastrophic bleeding and embolism. The knowledge may guide the emergency physician for a quicker cannulation of the veins.
Keywords: common trunk; external jugular vein; retromandibular vein